Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Kas Terhadap Perencanaan Dan Pengendalian Keuangan - Desy Ismah Anggraini; Pramandyah Fitah K; Amanatur Rosidah (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
An accounting information system is a system that is connected to each other as a whole, from procedures, forms, records, until finally financial reports can be created. There are two accounting information systems used by researchers, namely the cash receipt system and the cash disbursement system. The aim of this research is to find out how the accounting information system for cash receipts and disbursements is and the role of internal control at UD Dadhen Kurnia Abadi. UD Dadhen Kurnia Abadi is an MSME that operates in the catfish fillet industry so the organizational structure is more concise and the functions involved in a transaction are also quite small. Data was obtained by conducting interviews, observation and documentation. The research results show that the cash receipts and disbursements accounting information system running at UD. Dadhen Kurnia Abadi cannot be said to be good because it still uses manual recording which results in weaknesses, namely transactions recorded are not up to date so there are often discrepancies in recording so that the information produced is not accurate and precise and does not rule out the possibility of abuse of authority or embezzlement of funds. Apart from that, internal control is still less effective, there should be a strict separation of duties and responsibilities for each function, and the purchasing, receiving and cash functions should be separated.